Pb (II) biosorption from the aqueous solutions by raw and modified tea factory waste (TFW) - Nuhoglu, Y.; Ekmekyapar Kul, Z.; Kul, S.; Nuhoglu, C.; Ekmekyapar Torun, F. (SPRINGER, 2021)
The study is aimed to determine Pb (II) biosorption from synthetic wastewaters using natural and modified tea factory waste as biosorbent material. This process is carried out with this waste matter, which is found in large quantities, so cheap and has high metal adsorption ability. The sorption kinetic studies were determined as variations of initial pH value, particle size, initial Pb (II) and tea factory waste concentrations, stirring speed and temperature. Biosorption reached the equilibrium in 15 min. Zeta potential values of the biosorbent were defined in the range of pH 2 to 4. The adsorption isotherm models give the experimental values, and the thermodynamic characteristics of the patterns generally give insight about the sorption mechanism depending on the surface characteristics and affinity of the biosorbent. The biosorption mechanism was searched considering to Freundlich, Langmuir, BET and Temkin isotherm model, and the experimental adsorption values were conformed to Freundlich adsorption model. The optimum experimental conditions were investigated as pH 3.5, particle size of 0.125-0.25 mm, stirring speed of 200 rpm, biosorbent concentration of 7 g L-1 and 25 degrees C. In these conditions, the highest efficiency of biosorption was obtained as 94.07% and after the activating process the efficiency was reached to 97.73% at 70 mg L-1. The maximum Pb (II) removal capacity of raw tea factory waste was found to be 22.111 mg g(-1) at 200 mg L-1. The biosorption kinetics has complied with the pseudo-second-order model. Thermodynamic studies stated that this biosorption phenomenon was an endothermic process.
Keywords: Activated biosorbent; Raw biosorbent; Pb (II) removal; Tea factory waste; HEAVY-METALS; REMOVAL; LEAD; KINETICS; IONS; ADSORPTION; BIOMASS; CHROMIUM(VI); SORPTION; CR(VI); Environmental Sciences & Ecology